Conflicts over the admission policy of the University of Costa Rica during the 1950s - Molina Jiménez, Iván (Historia y Memoria de la Educación, 2019)
This article will show how the expansion of secondary education in Costa Rica during the 1950s lead to an increase in the number of students striving for access to higher education. The University of Costa Rica, at that time the only institution of its kind in the country, responded to the growing demand with an improvised and restrictive admission policy, which dashed the professional aspirations of hundreds of young people. The resulting dissatisfaction was expressed in numerous conflicts that confronted university authorities with students, parents, the media, various sectors of civil society and with the Ministry of Public Education. Due to this growing conflict, the University of Costa Rica decided in 1956 to eliminate for a brief period the admission tests and experiment with a new student selection system based on a General Studies course. However, this institutional reform did not provide the results expected by university authorities, so in 1959 a compulsory admission test was established for all those interested in entering higher education. The implementation of this initiative once again restricted access to higher education, as it was characterized by clear gender bias, with restrictions on women’s admission that favored men.